Views on agriculture in Telegrafo Mercantil of Rio de la Plata (1801-1802). A comparison with Spanish Enlightment (Quinto Sol, 2013)
This paper attempts to seek the economic basics in the approach to the agrarian problem, in the first printed newspaper in Buenos Aires: Telégrafo Mercantil, Rural, Económico e Historiográfico del Río de la Plata, published between 1801 adn 1802. Although some aspects of Telegráfo have already been studied, there is still a pending task: a contemporary systematization and analysis of its economic contents. Thus, we are interested in seeking which were the main conceptions, problema diagnoses, and agrarian proposals present in several articles on this newspaper. In this work, it is considered how agrarian news views were linked to the main economic arguments circulating by then in Río de la Plata, and -particularly- with economic debates in the Spain of the Enlightment. In general, the importance assigned to agricultura and encouragement to small and  middle peasants in those writings is stressed, as well as an intelectual reception considerably more complex tan mere adherence to the concepts of an economic school, though not for that less inmersed within the ecletic cultural world of hispanic Enlightment.
Keywords: Telégrafo Mercantil; Río de la Plata; colonial culture; enlightment; economic thought; agrarian debates; physiocracy